Heavy metal burden in the urine and cancer risk - Ke, Hongqian; Xie, Ning; Wu, Qian; Ye, Yuling; Fang, Yi (Frontiers in Oncology, 2025)
AimsThe purpose of this study was to evaluate the association between exposure to urinary heavy metals and cancer risk in adults in the United States.MethodsThe statistical data for this study were obtained from the National Health and Nutrition Examination Survey (NHANES) spanning 2009-2018. Participants lacking complete data on urinary heavy metals exposure burden and/or cancer status information were excluded. Urinary heavy metal concentrations were quantified using inductively coupled plasma mass spectrometry (ICP-MS). Cancer diagnoses were ascertained through self-reported medical histories. Multivariable-adjusted regression analyses and cubic smoothing plots were employed to assess independent associations between urinary heavy metal concentrations and cancer risk. Subgroup analyses were performed to assess result robustness.ResultsThe study included 7797 participants. Based on the first quartile (Q1), cadmium quartiles showed odds ratios (95% CIs) of 1.20 (0.92, 1.66) 1.50 (1.16, 1.94) and 1.57 (1.22, 2.03) for cancer prevalence (P = 0.0008). Cobalt quartiles were 1.22 (0.98, 1.54), 1.24 (0.98, 1.56), and 1.43 (1.13, 1.80) compared to the first quartile (Q1) (P = 0.0053). In comparison with the first quartile (Q1), Lead quartiles were 0.99 (0.77, 1.27), 1.06 (0.83, 1.35), and 1.06 (0.83, 1.35) (P = 0.0011). In the RCS plot, the association between log2-transformed urinary metal levels and cancer risk was not linear(P<0.05). An analysis of subgroups confirmed the robustness of the results.ConclusionElevated urinary heavy metal concentrations among U.S. adults demonstrated a significant association with increased cancer risk. These findings suggest that mitigating exposure to urinary heavy metals should be prioritized as a preventive strategy for cancer control.